The complete mitochondrial genome of Axis porcinus (Mammalia: Cervidae) from Victoria, Australia, using MiSeq sequencing. Issue 2 (12th December 2017) - Hill, Erin; Linacre, Adrian M. T.; Toop, Simon; Murphy, Nicholas P.; Strugnell, Jan M.
Abstract: The mitochondrial genome of the hog deer ( Axis porcinus ) was sequenced using an Illumina MiSeq. The assembled genome consists of 16, 351 bp, and shared a 99.8% similarity to the published chital deer ( Axis axis ) genome, suggesting that they belong to the same species. Further research is ongoing to understand why these mitochondrial genomes are highly similar.